2018
DOI: 10.3390/w10050622
|View full text |Cite
|
Sign up to set email alerts
|

Indirect Damage of Urban Flooding: Investigation of Flood-Induced Traffic Congestion Using Dynamic Modeling

Abstract: In many countries, industrialization has led to rapid urbanization. Increased frequency of urban flooding is one consequence of the expansion of urban areas which can seriously affect the productivity and livelihoods of urban residents. Therefore, it is of vital importance to study the effects of rainfall and urban flooding on traffic congestion and driver behavior. In this study, a comprehensive method to analyze the influence of urban flooding on traffic congestion was developed. First, a flood simulation wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 22 publications
0
19
0
Order By: Relevance
“…Authors of paper [9] carried out a study and found a relationship between the duration of floods due to rainfall in some parts of China and the behavior of drivers, which led to traffic jams. They revealed in a simulation process that the behavior of a driver had a different impact on the formation of traffic jams of different durations.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
See 1 more Smart Citation
“…Authors of paper [9] carried out a study and found a relationship between the duration of floods due to rainfall in some parts of China and the behavior of drivers, which led to traffic jams. They revealed in a simulation process that the behavior of a driver had a different impact on the formation of traffic jams of different durations.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…Formulas (8) and (9) for the assessment of the probability of an accident at sections of a transport network and at transport nodal points with an individual traffic participant considering model (10)…”
Section: Assessment Of the Probability Of An Accident With An Indimentioning
confidence: 99%
“…We constructed Chicago design storms [43,44] with four different return periods (2, 10, 50, and 100 years) with a rainfall duration of 2 h based on the following Nanjing storm intensity equation, which was derived from local rainfall records for more than 60 years: i = 64.300 + 53.800lgP (t + 32.900) 1.011 (9) where i is the rainfall intensity (mm/min), t is the rainfall duration (min), and p is the return period (year) of the rainfall event. We chose a rainfall duration of 2 h for the modeling and simulation because the Chicago hyetograph with a rainfall duration of 2 h is considered an appropriate way to simulate extreme rainfall in China [45,46]. The error would increase if a storm longer than 2 h was simulated [45,46].…”
Section: Scenario Designmentioning
confidence: 99%
“…We chose a rainfall duration of 2 h for the modeling and simulation because the Chicago hyetograph with a rainfall duration of 2 h is considered an appropriate way to simulate extreme rainfall in China [45,46]. The error would increase if a storm longer than 2 h was simulated [45,46]. Therefore, we designed 16 scenarios for the three sub-basins, as listed in Table 2.…”
Section: Scenario Designmentioning
confidence: 99%
“…As for the simulation models, in the existing studies, agent-based model (ABM) has been suggested as an appropriate tool to solve the kind of complex system problems such as emergency evacuation. ABM is a type of computational model that can provide the most natural description and simulation of complex adaptive systems, and implement the assumptions of model [15]. Through the simulation of the behaviors and interaction of autonomous agents in the ABM, the dynamic feedback of subsystem components, their inherent complexities and their effects on the system can be captured.…”
Section: Introductionmentioning
confidence: 99%